Tropical environmentalism of the ‘Malayu’ public realm-A reconstruction of traditional urban climatic ‘sanctuaries’ - Jahn Kassim, Puteri Shireen; Ibrahim, Illyani; Kamaruddin, Kamariah; Salleh, Elias; Mohd Nawawi, Norwina (WMIT Group Sdn Bhd, 2018)
The ‘Malay kedatuan’ refers to the traditional administrative centres of the Malay world which represent the public realm of a socio-cultural urbanized realm of the past. 16th century Melaka, 18th century Kedah, Terengganu and Riau-Lingga centres had at one time, constituted Sultanate-centered urban configurations, which now exist only in partial reconstructions, documents, lithographs and models. Surviving forms include Alor Setar, parts of Kota Bahru and Kuala Kangsar (Malaysia) and Pontianak, Kalimantan. ‘Archetypical’ refer to recurring generic configurations in which palaces, key buildings, were sited close to each other concerning river and sea. These sanctuaries embody key bioclimatic principles characterising the age-old ‘climatic fit’ of the Malay house, which were also reflected in such archetypes, which remain less discussed in the field of urban design. The traditional Malay public realm had mainly centred around palaces, and represent the axis of life during traditional times. These have now undergone extensive postcolonial layering. The paper reports on a reconstruction process which attempts to reconstruct the ‘vernacular’ including building and urban spaces, to learn from past traditional archetypes that have approximated the ideal tropical city, which utilised ecological resources to characterise urban spaces and had achieved comfort conditions through key passive means and key environmental features, such orientation, urban configurations, pathways, public space, shaded spaces and bioclimatic architecture. The paper highlights these features as lessons towards low carbon strategies.